Effect of shape-memory alloy NiTi fiber on microstructure and mechanical properties of continuous ceramic Al2O3 fiber-reinforced Ti/Al3Ti metal–intermetallic laminated composite. (17th April 2020) - Han, Yuqiang; Zhu, Junyi; Yan, Haoran; Lin, Chunfa; Zhao, Zhilei; Pan, Xuecong; Wang, Siyu
Shape-memory alloy titanium nickel (NiTi) fiber was introduced into continuous ceramic aluminum oxide (Al2 O3 ) fiber-reinforced titanium–titanium trialuminide metal–intermetallic laminated (CSMAFR-MIL) composite using vacuum hot pressing (HP) sintering method to improve the microstructure and mechanical properties of the composite. Scanning electron microscopy, energy-dispersive spectroscopy, and X-ray diffraction techniques were employed to characterize the microstructure of the novel CSMAFR-MIL composite. Besides, the tensile tests were carried out on continuous Al2 O3 fiber-reinforced Ti-Al metal–intermetallic laminated (CFR-MIL) composite and the CSMAFR-MIL composite to explore the influence of NiTi fiber additive on mechanical behavior of the CFR-MIL composite. The experimental results showed that the intermetallic layer including Al3 Ti, Al3 Ti0.8 V0.2, Al3 Ni intermetallics but without residual NiTi fiber was generated via the reactions of liquid Al with NiTi fiber and Ti foil during preparation. Moreover, owing to the addition of NiTi fiber, intermetallic centerline was prevented effectively to form in the CSMAFR-MIL composite. Moreover, the elemental diffusion occurred between the Al2 O3 fiber and the intermetallic, revealing that the metallurgical bonding was formed during the fabrication process. Furthermore, the CSMAFR-MIL composite possessed higher strength and superior ductility than those of CFR-MIL composite attributed to the microstructure optimization.